Analysis of goals scored in the 2010 world cup soccer tournament held in South Africa - Njororai, W. W. S. (Journal of Physical Education and Sport, 2013)
Purpose: To analyze the pattern and trends of the goals scored during the 2010 world cup soccer tournament held in South Africa to derive the latest technical and tactical innovations with the hope of applying them at the lower echelons of the game. Methodology: The study was a retrospective one as data were derived from the FIFA (2010) data base. The analysis centered on number of goals; parts of the body used to score; distance from goal; timing of goals in minutes; nature of play preceding a goal; score at half time and winning of the game; open play and set pieces; and the position of the scorers. Data were analyzed and descriptively presented in form of tables and figures. Results: The scoring rate of the world cup was 2.27 goals per match, which is the second lowest in the history of the world cup which was inaugurated in 1930. There were more goals from open play (75.86%) than from set pieces (24.14%); most goals came via shots (108) rather headers (26); strikers scored majority of the goals (53.10%), followed by midfielders (34.48) and defenders (11.04%); more goals were scored in the second half especially in the last 15 minutes of normal regulation time and more goals were scored from within the penalty box than outside. Conclusions: Coaches have to focus on improving the technical and tactical build up into the penalty area; encourage more goal attempts within the penalty box; emphasize and perfect set piece execution; prudently utilize substitution to impact the game in the second half, perfect crossing and headers and to enhance the physical conditioning of the players to enable them play out the entire game without suffering physical deterioration which causes teams to make defensive errors leading to goals in the last 15 minutes of matches.